Analisis Determinasi Pertumbuhan Ekonomi Studi Kasus di Indonesia - Nur Syamsiyah; Yudhistira Ardana; Muhamad Rahman Bayumi (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2022)
Economic growth is still an important goal in the economy of a country, especially for developing countries like Indonesia. If the real Gross Domestic Product (GDP) experiences growth, then the country's economy will grow well. This study will discuss the short-term and long-term effects of taxes, Zakat, Infaq and Alms (ZIS) and inflation on economic growth in Indonesia. This study uses the Error Correction Model with quarterly time series data starting from 2010-2020. The results of the study show that in the short term inflation has no significant positive effect on Indonesia's economic growth, while taxes have an insignificant negative effect and ZIS has a significant negative effect. In the long term, the tax and ZIS variables have a significant positive effect, while the inflation variable has a significant negative effect on economic growth in Indonesia.